2011
DOI: 10.1027/1618-3169/a000065
|View full text |Cite
|
Sign up to set email alerts
|

Coactive Processing of Dimensionally Redundant Targets Within the Auditory Modality?

Abstract: Previous reaction time studies have demonstrated coactivation processes within the visual modality for redundant stimuli that differ in two dimensions (e.g., shape and color). The present study provides novel results of analogous processes within the auditory modality. A redundant-target effect (RTE) was obtained in a Go/NoGo experiment using tones that differed in location and/or frequency. Participants were asked to respond to a specific tone location (e.g., left) and/or tone frequency (e.g., 200 Hz) of audi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…Due to their particular strength in distinguishing the dynamic properties of systems, response time based measures such as the capacity coefficient (Townsend & Nozawa, 1995; Townsend & Wenger, 2004) and the related Race Model Inequality (Miller, 1982) have been gaining employment in both basic and applied sectors of cognitive psychology. The purview of application of these measures includes areas as diverse as memory search (Rickard & Bajic, 2004), visual search (Krummenacher, Grubert, & Müller, 2010; Weidner & Muller, 2010), visual perception (Eidels, Townsend, & Algom, 2010; Scharf, Palmer, & Moore, 2011), auditory perception (Fiedler, Schröter, & Ulrich, 2011), flavor perception (Veldhuizen, Shepard, Wang, & Marks, 2010), multi-sensory integration (Hugenschmidt, Hayasaka, Peiffer, & Laurienti, 2010; Rach, Diederich, & Colonius, 2011) and threat detection (Richards, Hadwin, Benson, Wenger, & Donnelly, 2011). …”
mentioning
confidence: 99%
“…Due to their particular strength in distinguishing the dynamic properties of systems, response time based measures such as the capacity coefficient (Townsend & Nozawa, 1995; Townsend & Wenger, 2004) and the related Race Model Inequality (Miller, 1982) have been gaining employment in both basic and applied sectors of cognitive psychology. The purview of application of these measures includes areas as diverse as memory search (Rickard & Bajic, 2004), visual search (Krummenacher, Grubert, & Müller, 2010; Weidner & Muller, 2010), visual perception (Eidels, Townsend, & Algom, 2010; Scharf, Palmer, & Moore, 2011), auditory perception (Fiedler, Schröter, & Ulrich, 2011), flavor perception (Veldhuizen, Shepard, Wang, & Marks, 2010), multi-sensory integration (Hugenschmidt, Hayasaka, Peiffer, & Laurienti, 2010; Rach, Diederich, & Colonius, 2011) and threat detection (Richards, Hadwin, Benson, Wenger, & Donnelly, 2011). …”
mentioning
confidence: 99%
“…When the signals are different enough to be processed as two discrete pieces of information, the coactivation of separate perceptual modules occurs and causes an RSE (Mordkoff & Danek, 2011). This has been demonstrated in both visual (Mordkoff & Yantis, 1993) and auditory (Fiedler et al, 2011;Schröter et al, 2007) experiments in which two signal dimensions of one perceptual object were manipulated. For example, Mordkoff and Yantis (2003) showed that redundant signals in different perceptual dimensions, such as shape (e.g., X) and color (e.g., green), elicited coactivation (Experiments…”
Section: Introductionmentioning
confidence: 93%
“…Under this arrangement, the target location probability was equal across locations, such that information from two locations was equally salient and important for target detection. Moreover, a potential anticipation for redundant-target trials can be eliminated because only one-fourth of the trials contained dots at both locations (Fiedler, Schröter, & Ulrich, 2011;Mordkoff & Yantis, 1991;Townsend & Nozawa, 1995).…”
Section: Methodsmentioning
confidence: 99%